2020
DOI: 10.5114/fmpcr.2020.95311
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome is associated with novel inflammatory markers derived from hemogram parameters

Abstract: Background. Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder that is associated with sub-clinical inflammation. Some hemogram parameters are thought to be novel inflammatory markers. Objectives. We aimed to study novel inflammatory markers derived from hemograms and to compare them to those in healthy subjects. Material and methods. The platelet distribution width (PDW), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-lymphocyte ratio (MLR) of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 33 publications
4
97
1
Order By: Relevance
“…The suggested mechanism of accelerated clearance or consumption of platelets during malarial infection includes disseminated intravascular coagulation (DIC), immune-mediated destruction, pooling within the reticuloendothelial system, sequestration in the microcirculation, and malaria-mediated apoptosis [ 13 – 16 ]. In contrast to this study, a study was reported no association between the mean platelet count and irritable bowel syndrome [ 35 ]. A study was reported no difference between mean platelet count and TSH levels between the malignant thyroid nodule group and benign nodule group [ 36 ].…”
Section: Discussioncontrasting
confidence: 83%
“…The suggested mechanism of accelerated clearance or consumption of platelets during malarial infection includes disseminated intravascular coagulation (DIC), immune-mediated destruction, pooling within the reticuloendothelial system, sequestration in the microcirculation, and malaria-mediated apoptosis [ 13 – 16 ]. In contrast to this study, a study was reported no association between the mean platelet count and irritable bowel syndrome [ 35 ]. A study was reported no difference between mean platelet count and TSH levels between the malignant thyroid nodule group and benign nodule group [ 36 ].…”
Section: Discussioncontrasting
confidence: 83%
“…PLR is also identified as a diagnostic tool in inflammatory bowel syndrome. 23 Similarly, Mean…”
Section: Platelet-to-lymphocyte Ratiomentioning
confidence: 99%
“…22 It can also as a diagnostic tool in inflammatory bowel disease. 23 This ratio has also been considered as a determinant of outcomes of various malignancies and coronary arterial diseases as well as patients suffering from recurrent ulcerative colitis. All these conditions are associated with overt inflammation as in COVID-19.…”
Section: Neutrophil-to-lymphocyte Ratiomentioning
confidence: 99%
“…NLR has been suggested to be associated with cardiac arrhythmia, 4 thyroiditis, 5 malignant nodules, 6 diabetes mellitus, 7 inflammatory bowel disease, 8 and irritable bowel syndrome. 9 All these conditions are characterized with overt or subtle inflammation, alike with IgA nephropathy. Yang H 10 found that NLR could predict the response to corticosteroids in IgAN.…”
Section: Backg Rou N Dmentioning
confidence: 99%